Deforestation, Land Taxes and Development - Matthias Kalkuhl; Ottmar Edenhofer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper combines neoclassical growth theory with the von Th nen approach of land conversion to model deforestation and land allocation decisions in an intertemporal general equilibrium context suitable for developing countries. Analyzing the impact of several forest conservation policies, including international transfers under a REDD+ scheme, emphasized the role of taxes on non-forest land as effective and powerful policy that has been largely neglected so far.The findings of our equilibrium analysis are in stark contrast to the conventional economic wisdom that taxes on land are allocation neutral. As we model deforestation as one investment decision besides investment into physical capital stocks, land taxes may not only increase forest conservation levels but also overall capital stocks and output. We identify the conditions that lead to this double-dividend effect and apply them to data for a set of countries, concluding that forest conservation, e.g. implemented by land taxes, can have this positive effect for many developing countries. Additionally, we reassess Borlaug s hypothesis and Jevons paradox in a general-equilibrium context and design a land tax scheme that is robust to agricultural yield increases.
Keywords: D90; H23; O13; 330